Islamic development bank’s microfinance support programme and the growth of small scale enterprises in Nigeria (2014)
It is obvious that poverty is endemic in Nigeria. One of the reasons contributing to this is uncomplimentary situation is lack of employment for the majority of Nigerians. Several attempts aimed at creating employment have been embarked upon at governmental and non-governmental levels, with lithe effect. On the other side, the Islamic Development Bank (IDB), to which Nigeria is a key member, has been actively involved in the support of Small Scale Enterprises in some member countries through skillful carved sustainable non-interest base microfinance programme. Most studies on microfinance in Nigeria have not paid attention to the application of the IDB’s Microfinance Support Programme to Nigeria. Hence, this paper fills the gap through examining some of the past and present attempts of the government at providing microcredit and microfinance to Nigerians. It also considers the operational strategy utilized by the IDB at bringing sustainable microfinance scheme to the doorsteps of the poor in member countries. Consequently, it advocates this laudable microfinance scheme for Nigeria, arguing that if this is done, mass employment accompanied by best practices capable of reducing poverty would be injected into Nigeria.